Pro JavaScript for Web Apps - Freeman, Adam.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
JavaScript is the engine behind every web app, and a solid knowledge of it is essential for all modern web developers. Pro JavaScript for Web Apps gives you all of the information that you need to create professional, optimized, and efficient JavaScript applications that will run across all devices. It takes you through all aspects of modern JavaScript application creation, showing you how to combine JavaScript with the new features of HTML5 and CSS3 to make the most of the new web technologies. The focus of the book is on creating professional web applications, ensuring that your app provides the best experience for your users, with smooth and responsive control and feedback and an intuitive and optimized interface. You will learn how to take a basic application and bring it up to a professional level while making sure that it remains bullet-proof and bug free. Pro JavaScript for Web Apps will also enhance your development workflow using jQuery to streamline the process and freeing you to spend more time on the important parts of your app while the framework deals with the mundanity. The best app experiences are a combination of a beautiful idea with flawless execution. If you have the ideas, Pro JavaScript for Web Apps will help you craft them into a phenomenal app.
Keywords: Computer science; Computer Science; Computer Science, general